Tuesday

September 2, 2014

September 2, 2014

Posted by **sh** on Thursday, May 28, 2009 at 4:46am.

(sinx+tanx)/(cosx+1)=tanx

RS: (sinx+(sinx/cosx))/(cosx+1)

((sinxcosx/cosx)+(sinx/cosx))x 1/(cosx+1)

sinx(cosx+1)/cosx x 1/(cosx+1)

sinx/cosx = tanx

RS = LS

How did sinxcosx/cosx turn to sinx(cosx+1)?

- Math -
**sh**, Thursday, May 28, 2009 at 4:49amsolved

**Answer this Question**

**Related Questions**

Trigonometry. - ( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! ...

Trigonometry Check - Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [...

Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...

maths - trigonometry - I've asked about this same question before, and someone ...

Mathematics - Trigonometric Identities - Prove: (tanx)(sinx) / (tanx) + (sinx...

Trig........ - I need to prove that the following is true. Thanks (cosx / 1-sinx...

Math - Verify the identity . (cscX-cotX)^2=1-cosX/1+cosX _______ sorry i cant ...

Math - Im really struggling with these proving identities problems can somebody ...

Math 12 - Simplify #1: cscx(sin^2x+cos^2xtanx)/sinx+cosx = cscx((1)tanx)/sinx+...

Trigonometry - Simplify #1: cscx(sin^2x+cos^2xtanx)/sinx+cosx = cscx((1)tanx)/...